IMPLEMENTASI ROLE PLAYING PERANCANG PERHIASAN SEBAGAI STIMULASI PERKEMBANGAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI KIDZANIA SURABAYA - H Tarulibasa Siahaan, Gloria; Samawi, Ahmad; Tirtaningsih, Munaisra Tri (Dharmas Education Journal (DE_Journal), 2024)
This research was conducted with the aim of seeing the implementation of role-playing jewelry designers at KidZania Surabaya edutainment rides as a stimulation of children's fine motor development. The type of research used is qualitative research will involve data collection methods through interview data, observation and documentation. This qualitative research uses a case study design with the aim of understanding and finding in-depth understanding of a situation, group, or individual. This research will analyze data using the Miles, Huberman and Saldana model which is divided into four stages. The results of the study found that the implementation of jewelry designer role play at KidZania Surabaya has a positive impact felt by parents of visitors, children, and also employees who are involved there. Through this activity, the jewelry designer's establishment is able to stimulate on other aspects of early childhood development such as cognitive development and social-emotional development.